Extending NGOMSL Model for Human-Humanoid Robot Interaction in the Soccer Robotics Domain - Rajesh Elara Mohan; Carlos Antonio Acosta Calderon; Changjiu Zhou; Pik Kong Yue (Applied Bionics and Biomechanics)
In the field of human-computer interaction, the Natural Goals, Operators, Methods, and Selection rules Language (NGOMSL) model is one of the most popular methods for modelling knowledge and cognitive processes for rapid usability evaluation. The NGOMSL model is a description of the knowledge that a user must possess to operate the system represented as elementary actions for effective usability evaluations. In the last few years, mobile robots have been exhibiting a stronger presence in commercial markets and very little work has been done with NGOMSL modelling for usability evaluations in the human-robot interaction discipline. This paper focuses on extending the NGOMSL model for usability evaluation of human-humanoid robot interaction in the soccer robotics domain. The NGOMSL modelled human-humanoid interaction design of Robo-Erectus Junior was evaluated and the results of the experiments showed that the interaction design was able to find faults in an average time of 23.84 s. Also, the interaction design was able to detect the fault within the 60 s in 100% of the cases. The Evaluated Interaction design was adopted by our Robo-Erectus Junior version of humanoid robots in the RoboCup 2007 humanoid soccer league.